1994
DOI: 10.1007/bf00158286
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of the paraneuronal endocrine cells in the skin, gills and the airways of fishes as determined by immunohistochemical and histological methods

Abstract: The neuro-endocrine cells of fish skin and respiratory surfaces, and their bioactive secretion as far as is known, are reviewed, and compared with similar elements in tetrapods, particularly amphibians. In the skin of teleost fish, immunohistochemistry has shown that Merkel cells react for serotonin, neuron-specific enolase and enkephalins. The pharmacology is not established in dipnoans or lampreys. In some teleosts, neuromasts react for substance P and leu-enkephalins; substance P is also reported from some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 111 publications
2
49
0
3
Order By: Relevance
“…Fish have specialized neuroepithelial cells (NECs) in their gill arches, positioned to sense both partial pressure of gases (e.g. P CO2 and P O2 ) in the blood and in the external environment (Bailly et al, 1992;Zaccone et al, 1994;Perry et al, 2009). Increases in external P CO2 stimulate these gill chemoreceptors and initiate a cardiorespiratory response, such as hyperventilation (Burleson and Smatresk, 2000;Perry and Abdallah, 2012;Heuer and Grosell, 2014) to minimize the effects of elevated P CO2 on blood pH (Gilmour, 2001;Perry and Abdallah, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Fish have specialized neuroepithelial cells (NECs) in their gill arches, positioned to sense both partial pressure of gases (e.g. P CO2 and P O2 ) in the blood and in the external environment (Bailly et al, 1992;Zaccone et al, 1994;Perry et al, 2009). Increases in external P CO2 stimulate these gill chemoreceptors and initiate a cardiorespiratory response, such as hyperventilation (Burleson and Smatresk, 2000;Perry and Abdallah, 2012;Heuer and Grosell, 2014) to minimize the effects of elevated P CO2 on blood pH (Gilmour, 2001;Perry and Abdallah, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the medaka, there were also many tissues that appeared to be S-100-positive, but strong signal was restricted to the nervous system, and neurosensory tissues in the skin, and nasal and auditory cavities. S-100-positive neurosensory cells have also been detected in the oscar (Astronotus ocellatus) (28), rainbow trout (Salmo gairdnerii R.) (14), and other species (36), and neuroepithelioma in medaka has been previously shown to be focally positive for S-100 (33).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated that other neurochemical candidates may include nitric oxide or catecholamines (Zaccone et al, 2006;Burleson et al, 2006;Milsom and Burleson, 2007), and a variety of neuropeptides may also be involved (for reviews, see Zaccone et al, 1994;Zaccone et al, 1997). It is conceivable that the neurochemical basis of O 2 sensing in the gill may involve multiple neurotransmitters or neuropeptides and, perhaps, a diversity of excitatory, inhibitory and modulatory mechanisms, as has been described in the mammalian O 2 -sensing organ, the carotid body (González et al, 1994;Nurse, 2005;Prabhakar, 2006;Lahiri et al, 2006).…”
Section: Role Of Innervation In O 2 Sensingmentioning
confidence: 99%
“…NECs store 5-HT in cytoplasmic synaptic vesicles near the plasma membrane (Fig. 5) and have a morphology and distribution that is highly conserved among fish (Dunel-Erb et al, 1982;Zaccone et al, 1994;Zaccone et al, 1997;Sundin et al, 1998a;Jonz and Nurse, 2003;Saltys et al, 2006;Coolidge et al, 2008). Experiments have demonstrated that gill NECs isolated from zebrafish respond to hypoxia with K + channel inhibition and membrane depolarization, thus confirming their O 2 sensitivity, and a cellular model for O 2 sensing in fish has been proposed where Ca 2+ -dependent release of neurotransmitter results in activation of postsynaptic sensory nerve fibres (Jonz et al, 2004).…”
Section: Role Of Innervation In O 2 Sensingmentioning
confidence: 99%